Is fluoride the best we've got? The most common toothpaste active ingredients and their influence on caries and oral health: A brief review of the literature - Kowalska, Klaudia; Weronika Kiełt; Julia Kozłowska; Gabriela Broniec; Barbara Wajdowicz; Aleksandra Kudła; Rozalia Czapiewska; Aleksandra Dziewulska; Aleksandra Wróbel; Laura Pacek (Journal of Education, Health and Sport, 2024)
Aim of the study Toothpaste is a paste or gel to be used with a toothbrush to maintain and improve oral health and aesthetics. Nowadays there is a great variety of ingredients that might have different effects on caries development or oral health in general. Society continues to seek ways to replace fluoride or include more natural ingredients in everyday hygiene products. The aim of our study is to present current knowledge of various ingredients in toothpastes regarding their influence on teeth and intraoral soft tissues and the possibility of replacing fluoride with other substances. Material and methods Our review is based on the analysis of materials collected in„Pubmed”, „Google Scholar” and other scientific articles using keywords: „toothpaste”, „fluoride”, „ingredients”, “hydroxyapatite”, „chlorhexidine”, “triclosan”, “propolis”, “aloe vera”, “charcoal”, “oleanolic acid”, “SLS”, “xylitol” Conclusions Despite numerous studies, there is space for further research in finding substances that might improve toothpastes with or without extracting fluoride from them. Fluoride has the most proven effectiveness in caries prevention, with fluorosis as its most damaging side effect, while hydroxyapatite shows promising results. Although, there are many substances that might be useful in oral health care products.